How Secure is the EU Energy Policy after the Ukraine Crisis? - Gümüş, Yasin Kerem (International Journal of Energy Economics and Policy, 2015)
The political tensions which have emerged between Russia and the West after Ukraine crisis put the EU energy security problem at the top of the EU agenda. While dependency on Russia and bilateral agreements appear to be weaknesses of EU energy security, decline in demand among EU members and improvement in energy efficiency pose to be strengths. The EU has also some opportunities to deal with the crisis such as decline in oil prices and diversification of energy supply while falls in domestic energy production and Ukrainian question pose threats to the EU energy security. Keywords: Energy Policy; EU; Ukraine Crisis; Energy Security JEL Classifications: Q41; Q48